Pregnancy outcomes in infertile patients with endometrial hyperplasia with or without atypia undergoing in vitro fertilization: the early-follicular long protocol is superior to midluteal long protocol - An, Huiling; Li, Tongjie; Huang, Kai; Shi, Hao; Wang, Chen; Chu, Ting; Zhai, Jun (Frontiers in Endocrinology, 2024)
Background: Although in vitro fertilization (IVF) in infertile patients with endometrial hyperplasia is common after drug treatment, the pregnancy outcomes are often unsatisfactory. Till date, no studies have reported the outcome of patients with endometrial hyperplasia treated using early-follicular long (EL) protocol and midluteal long (ML) protocol. Objective: To evaluate the pregnancy outcomes and disease prognosis of patients with endometrial hyperplasia with or without atypia undergoing IVF treatment with EL protocol or ML protocol. Methods:This was a retrospective study in university-affiliated reproductive medical center.A total of 138 patients with endometrial hyperplasia undergoing IVF treatment were included to compare the pregnancy outcomes and disease prognosis between EL and ML protocols.We further matched 276 patients with normal endometrium to compare the pregnancy outcomes between patients with endometrial hyperplasia and patients with normal endometrium under different controlled ovarian stimulation (COS) protocol. Results: In patients with endometrial hyperplasia, the clinical pregnancy rate (CPR) and live birth rate (LBR) were significantly higher in EL protocol than in ML protocol (61.8% vs. 43.5%, P=0.032; 50.0% vs. 30.6%, P= 0.022). In the ML protocol, patients with endometrial hyperplasia had significantly lower CPR and LBR than those with normal endometrium (43.5% vs. 59.7%, P=0.037; 30.6% vs. 49.2%, P=0.016). While in the EL protocol, they achieved similar CPR and LBR as patients with normal endometrium (61.8% vs. 69.7%, P=0.232; 50.0% vs. 59.9%, P=0.156). In patients with endometrial hyperplasia, COS protocol was an independent factor affecting clinical pregnancy (adjusted odds ratio [OR] 2.479; 95% confidence interval [CI] 1.154-5.327) and live birth (adjusted OR 2.730; 95% CI 1.249-5.966).After 1-10 years of follow-up, no significant difference was found in the recurrence rate of endometrial lesions between both treatment groups. Conclusions: For patients with endometrial hyperplasia undergoing IVF treatment, the EL protocol is superior to ML protocol, and in the EL protocol, they can achieve similar pregnancy outcomes as patients with normal endometrium.